GERAKAN POLITIK PADA MASA PENJAJAHAN JEPANG - Legawa, I Wayan (Jurnal Sejarah dan Budaya, 2009)
Abstract: The objective of this article to show political movement during Japanese colonialism era in Indonesia. The fields of political movement described are in many fields such as politics, economy, social, culture and military. There is a movement pattern, including movement tactics and strategy that supports and resists to Japanese Government. The movement supporting Japanese Government is borned by Japan, namely Gerakan Tiga A, Barisan Pemuda Asia Raya, POETERA, Jawa Hokokai, Tjoeo Sangi In, Seinendan, Keibodan, Barisan Pelopor, Heiho, Tonari Gumi, PETA, Gerakan Rakyat Baru. At the opposite side, there are several independent movements that rebel to Japan, such as Angkataan Muda Indonesia, Gerakan Angkatan Barau Indonesia, Ika Daigaku, Pemberontakan Sukamanah, Pemberontakan Karanagampeel